2021
DOI: 10.1094/pdis-04-21-0693-re
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Colletotrichum fructicola and Colletotrichum siamense of Peach in China to Multiple Classes of Fungicides and Characterization of Pyraclostrobin-Resistant Isolates

Abstract: Anthracnose, mainly caused by Colletotrichum gloeosporioides species complex including C. fructicola and C. siamense, is a devastating disease of peach. The chemical control has been widely used for years and management failures have increased towards commonly used fungicides. Therefore, screening of sensitivity of Colletotrichum spp. to fungicides with different modes of action is needed to make proper management strategies for peach anthracnose. In this study, sensitivity of 80 isolates of C. fructicola and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Meanwhile, all C. nymphaeae strains in this study have been confirmed to be resistant to carbendazim (MBC) [ 75 ]. C. nymphaeae was reported to be less sensitive to demethylation inhibitor (DMIs) fungicides (flutriafol and fenbuconazole) compared with C. fioriniae , C. fructicola , and C. siamense [ 21 ] and C. gloeosporioides was reported to be inherently tolerant to fludioxonil [ 76 , 77 ]. Most of the peach farms in China are small and there is vast diversity in the approaches to managing diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, all C. nymphaeae strains in this study have been confirmed to be resistant to carbendazim (MBC) [ 75 ]. C. nymphaeae was reported to be less sensitive to demethylation inhibitor (DMIs) fungicides (flutriafol and fenbuconazole) compared with C. fioriniae , C. fructicola , and C. siamense [ 21 ] and C. gloeosporioides was reported to be inherently tolerant to fludioxonil [ 76 , 77 ]. Most of the peach farms in China are small and there is vast diversity in the approaches to managing diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The five genotype mutations in CYP51A and CYP51B of C. siamense have not yet been reported in other Colletotrichum species. Recent studies showed that C. siamense isolates from peach in China were sensitive to prochloraz, while those from apple in Illinois of the United States were sensitive to propiconazole (Chechi et al 2019;Usman et al 2021). C. siamense isolates from strawberry in China were sensitive to difenoconazole, tebuconazole and prochloraz (Zhang et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…had higher sensitivity to pyraclostrobin than other strobilurin fungicides. 46,47) Several reasons are suspected to be associated with the higher ability of pyraclostrobin to inhibit the mycelial growth of CGSC. First, pyraclostrobin, recommended in 2002 for controlling strawberry anthracnose, was released later than azoxystrobin, kresoxim-methyl, and trifloxystrobin.…”
Section: Discussionmentioning
confidence: 99%